The prevalence of probable depression and probable anxiety, and associations with adverse childhood experiences and socio-demographics: A national survey in South Africa - Craig, Ashleigh; Rochat, Tamsen; Naicker, Sara N.; Mapanga, Witness; Mtintsilana, Asanda; Dlamini, Siphiwe N.; Ware, Lisa J.; Du Toit, Justin; Draper, Catherine E.; Richter, Linda; Norris, Shane A. (Frontiers in Public Health, 2022)
Objective and methods: Mental health problems among adults are a growing public health concern, and middle-income countries such as South Africa are disproportionally affected. Using a large scale nationally representative weighted survey, we assessed the prevalence of probable depression, probable anxiety, and adverse childhood experiences (ACEs), and explored associations between probable depression, probable anxiety, ACEs, socio-economic status, and demographic characteristics. Results: Nationally, 25.7%, 17.8% and 23.6% of respondents respectively reported scores of ≥10 on the Patient Health Questionnaire-9 (PHQ-9) and Generalised Anxiety Disorder-7 (GAD-7), indicating probable depression or probable anxiety, and an ACE score of ≥ 4 (high exposure). Overall probable depression prevalence across South Africa varied from 14.7% to 38.8%. Both probable depression and probable anxiety were more frequently reported among adults who were: retired and older (>65 years of age), and widowed, divorced, or separated; living in metropolitan areas; and only had primary school education. In a multivariable adjusted logistic regression, the likelihood of reporting probable depression or probable anxiety was also found to increase with each standard deviation increase in the ACE score (p<0.001), independent of other socio-demographic determinants. Conclusion: The prevalence of probable depression among respondents in South Africa varies significantly across the nine provinces. Furthermore, higher ACE score and several socio-demographic determinants were associated with a higher likelihood of probable depression and probable anxiety. Adult mental health services are urgently needed to identify groups of the population vulnerable to mental health problems for better targeting of interventions. Given the range of probable depression prevalence across the country, provincial level plans and resources should also reflect the burden of mental health problems in that province.